Privacy in dwellings: attitudes, visual and functional connections - Reis, Antônio Tarcísio da Luz (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper examines resident’s attitudes concerning the adequacy of visual privacy in 374 dwellings in 12 housing estates in the Metropolitan Region of Porto Alegre, and aspects associated to the visual connections, such as areas of isovists, the relationship between the mean number of visualized spaces and the mean number of spaces in the dwellings in each housing estate, and the type of spaces visualized. Aspects associated to the functional connections are also investigated, such as the type of connected spaces and the type of topological spaces in the dwelling system, revealing different possibilities of movement by residentes and visitors, the degree of integration of spaces and the difference factor, which measure the differences in the spatial configuration of the dwelling as represented by integration values. Data was collected through questionnaires, structured interviews and physical measurements, and analysed by non-parametric statistical tests and space syntax methods. Some of the main results indicate that some quantitative methods are more appropriate than others to predict the adequacy of visual privacy in the dwelling, and that the greater the homogenization of the spatial configuration, the greater the tendency for visual privacy related problems.